Cardiac Energy Dependence on Glucose Increases Metabolites Related to Glutathione and Activates Metabolic Genes Controlled by Mechanistic Target of Rapamycin. Issue 2 (24th February 2015) - Schisler, Jonathan C.; Grevengoed, Trisha J.; Pascual, Florencia; Cooper, Daniel E.; Ellis, Jessica M.; Paul, David S.; Willis, Monte S.; Patterson, Cam; Jia, Wei; Coleman, Rosalind A.
Abstract : Background: Long chain acyl‐CoA synthetases (ACSL) catalyze long‐chain fatty acids (FA) conversion to acyl‐CoAs. Temporal ACSL1 inactivation in mouse hearts ( Acsl1 H−/− ) impaired FA oxidation and dramatically increased glucose uptake, glucose oxidation, and mTOR activation, resulting in cardiac hypertrophy. We used unbiased metabolomics and gene expression analyses to elucidate the cardiac cellular response to increased glucose use in a genetic model of inactivated FA oxidation. Methods and Results: Metabolomics analysis identified 60 metabolites altered in Acsl1 H−/− hearts, including 6 related to glucose metabolism and 11 to cysteine and glutathione pathways. Concurrently, global cardiac transcriptional analysis revealed differential expression of 568 genes in Acsl1 H−/− hearts, a subset of which we hypothesized were targets of mTOR; subsequently, we measured the transcriptional response of several genes after chronic mTOR inhibition via rapamycin treatment during the period in which cardiac hypertrophy develops. Hearts from Acsl1 H−/− mice increased expression of several Hif1 α‐responsive glycolytic genes regulated by mTOR; additionally, expression of Scl7a5, Gsta1/2, Gdf15, and amino acid‐responsive genes, Fgf21, Asns, Trib3, Mthfd2, were strikingly increased by mTOR activation. Conclusions: The switch from FA to glucose use causes mTOR‐dependent alterations in cardiac metabolism. We identified cardiac mTOR‐regulated genes not previously identified in other cellular models, suggesting heart‐specific mTOR signaling. Increased glucose use also changed glutathione‐related pathways and compensation by mTOR. The hypertrophy, oxidative stress, and metabolic changes that occur within the heart when glucose supplants FA as a major energy source suggest that substrate switching to glucose is not entirely benign.